2018
DOI: 10.2967/jnumed.118.207993
|View full text |Cite
|
Sign up to set email alerts
|

PSMA-Targeted Radionuclide Therapy and Salivary Gland Toxicity: Why Does It Matter?

Abstract: Abbreviated title: Salivary gland toxicity after PSMA-Targeted Radionuclide Therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 10 publications
1
59
0
2
Order By: Relevance
“…The salivary glands are radiosensitive organs, and physiologic high binding of PSMA ligands may cause undesirable side effects (19,24). Xerostomia, a frequent but mild to moderate side effect after PRLT of mCRPC, decreases the patient's quality of life (19,(25)(26)(27).…”
mentioning
confidence: 99%
“…The salivary glands are radiosensitive organs, and physiologic high binding of PSMA ligands may cause undesirable side effects (19,24). Xerostomia, a frequent but mild to moderate side effect after PRLT of mCRPC, decreases the patient's quality of life (19,(25)(26)(27).…”
mentioning
confidence: 99%
“…The high uptake of 18 F‐FSU‐880 observed in the kidneys and salivary and lachrymal glands might reflect physiological PSMA expression in these organs. However, the reported PSMA expression in the salivary glands was rather low compared to the observed high probe uptake, and radiolabeled anti‐PSMA Ab did not show high salivary gland uptake, indicating that some additional mechanism related to the small molecular size should be considered . Although a preclinical study had shown that 18 F‐FSU‐880 is excreted exclusively from the kidneys, the amount of 18 F‐FSU‐880 excreted into urine during the PET 4/PET 5 interval was relatively low (8.0%‐13.2%), suggesting that more rigid hydration to accelerate diuresis would be beneficial in future studies to further reduce background activity and improve image contrast.…”
Section: Discussionmentioning
confidence: 90%
“…However, the reported PSMA expression in the salivary glands was rather low compared to the observed high probe uptake, and radiolabeled anti-PSMA Ab did not show high salivary gland uptake, 22,23 indicating that some additional mechanism related to the small molecular size should be considered. 24 Although a preclinical study had shown that 18 F-FSU-880 is excreted exclusively from the kidneys, 19 the amount of 18 15,16,25 and was also acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to our knowledge, kidney and salivary gland protection mediated by JHU-2545 represents the first example of a clinically viable method for enhancing the therapeutic index of PSMA radiotherapeutics. Salivary gland protection mediated by JHU-2545 may be of immediate clinical utility given that transient or irreversible xerostomia after PSMA radiotherapy has already been reported in a large number of cases (9,10,14). Results from a Phase 2 trial of 177 Lu-PSMA-617 in mCRPC found xerostomia to be a very common adverse event, occurring in 87% of patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant progress, clinical development of PSMA-targeted agents has been complicated by the physiologic expression of PSMA in normal tissues including salivary glands and kidneys (12,13) which exhibit avid uptake of PSMA radiopharmaceuticals during imaging and radiation dosimetry (5,8). Salivary gland uptake of PSMA radiotherapeutics can result in transient or permanent xerostomia, an adverse effect particularly problematic for alpha radionuclides (2,14). For example, 225 Ac-PSMA-617 recently showed striking efficacy in heavily pre-treated mCRPC patients (5/40 complete tumor control >2 years), but this impressive response was nearly matched by treatment discontinuation due to xerostomia (4/40) (2).…”
Section: Introductionmentioning
confidence: 99%